Kingdom of heaven - Scott, Ridley; Monahan, William; Twentieth Century Fox Home Entertainment ([Beverly Hills, Calif.] : Twentieth Century Fox Home Entertainment, 2005)
The story of blacksmith Balian who having lost his family, travels to Jerusalem during the crusades becoming a knight and a defender of the city in the process
Title from title screen
n.1 copy
Director of photography, John Mathieson ; film editor, Dody Dorn ; music, Harry Gregson-Williams
Casts: Orlando Bloom, Eva Green, Jeremy Irons, Liam Neeson
Keywords: Knights and knighthood -- Drama; Crusades -- Drama; Jerusalem -- Drama